Implementation of Principal Leadership at SMKN 2 Sungai Raya - Mening, Helaria (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research was conducted at SMKN 2 Sungai Raya, Kubu Raya Regency, with the aim of describing: (1) the implementation of the principal's leadership at SMKN 2 Sungai Raya, (2) the leadership style of the principal in carrying out his duties at SMKN 2 Sungai Raya. A qualitative analysis approach is used to explain the implementation of the principal's leadership at SMKN 2 Sungai Raya. The results of the study found that: 1) Principal leadership at SMKN 2 Sungai Raya is implemented through the principal's responsibility for main tasks and functions, working with teachers and paying attention to teachers, making firm and disciplined decisions at school, demonstrating the teacher's role as an educator who directs and acts as a motivator at school, becomes an administrator in the implementation of educational administrative services 2) The leadership style of the principal at SMKN 2 Sungai Raya is a charismatic leadership style that gives a downward pull force to carry out work without providing supervision and gives subordinates confidence in increasing competence in building excellent schools.Implementasi; Kepemimpinan; Kepala Sekolah.Penelitian ini dilaksanakan di SMKN 2 Sungai Raya Kabupaten Kubu Raya, dengan tujuan untuk mendeskripsikan tentang: (1) Implementasi kepemimpinan kepala sekolah di SMKN 2 Sungai Raya, (2) Gaya kepemimpinan kepala sekolah dalam melaksanakan tugasnya di SMKN 2 Sungai Raya. Pendekatan analisis kualitatif digunakan untuk menjelaskan pelaksanaan kepemimpinan kepala sekolah di SMKN 2 Sungai Raya. Hasil penelitian menemukan bahwa: 1) Kepemimpinan kepala sekolah SMKN 2 Sungai Raya diimplementasikan melalui tanggung jawab kepala sekolah terhadap tugas pokok dan fungsi, bekerja sama dengan guru dan memberikan perhatian kepada guru, mengambil keputusan yang tegas dan disiplin di sekolah, menunjukkan peran guru sebagai pendidik yang mengarahkan serta sebagai motivator di sekolah, menjadi administrator dalam pelaksanaan pelayanan administrasi pendidik 2) Gaya kepemimpinan kepala sekolah di SMKN 2 Sungai Raya adalah gaya kepemimpinan karismatik yang memberi gaya tarik ke bawahan untuk melaksanakan pekerjaan tanpa memberikan pengawasan serta memberikan bawahan kepercayaan dalam meningkatkan kompetensi dalam membangun sekolah yang unggul.Implementation; Leadership; Headmaster.This research was conducted at SMKN 2 Sungai Raya, Kubu Raya Regency, with the aim of describing: (1) the implementation of the principal's leadership at SMKN 2 Sungai Raya, (2) the leadership style of the principal in carrying out his duties at SMKN 2 Sungai Raya. A qualitative analysis approach is used to explain the implementation of the principal's leadership at SMKN 2 Sungai Raya. The results of the study found that: 1) Principal leadership at SMKN 2 Sungai Raya is implemented through the principal's responsibility for main tasks and functions, working with teachers and paying attention to teachers, making firm and disciplined decisions at school, demonstrating the teacher's role as an educator who directs and acts as a motivator at school, becomes an administrator in the implementation of educational administrative services 2) The leadership style of the principal at SMKN 2 Sungai Raya is a charismatic leadership style that gives a downward pull force to carry out work without providing supervision and gives subordinates confidence in increasing competence in building excellent schools.